2011
DOI: 10.1007/s00428-011-1138-2
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial marker expression does not rule out a diagnosis of Ewing’s sarcoma family of tumours

Abstract: Epithelial marker expression has been reported in Ewing's sarcoma family of tumors (ESFT). However, cytokeratin (CK), epithelial membrane antigen (EMA), and carcino embryonic antigen (CEA) prevalence has not been assessed thoroughly in a large series of genetically confirmed ESFT. The aim of the present study is to confirm the presence of epithelial markers in a large group of ESFT tested genetically for any of their specific gene fusions and the differential diagnosis with other small round cell tumors. To es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 26 publications
(59 reference statements)
0
18
0
1
Order By: Relevance
“…During the study of the present case, we realized that the small cell carcinoma of the thyroid reported by Cruz et al, 12 which had a favorable clinical course (38 months of followup), was morphologically and immunohistochemically We admit that the distinction between CEFTE and PEEFT with prominent epithelial differentiation [13][14][15] is not clear cut. Nevertheless, the particular favorable evolution 5 The thyroid PEEFT of the thyroid reported by Adapa et al 6 was diagnosed in a 9-yearold child who remained free of disease for at least 6 years after chemotherapy with standard arm of COG-AEWS0031 Ewing sarcoma treatment protocol and right lobectomy plus isthmectomy.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…During the study of the present case, we realized that the small cell carcinoma of the thyroid reported by Cruz et al, 12 which had a favorable clinical course (38 months of followup), was morphologically and immunohistochemically We admit that the distinction between CEFTE and PEEFT with prominent epithelial differentiation [13][14][15] is not clear cut. Nevertheless, the particular favorable evolution 5 The thyroid PEEFT of the thyroid reported by Adapa et al 6 was diagnosed in a 9-yearold child who remained free of disease for at least 6 years after chemotherapy with standard arm of COG-AEWS0031 Ewing sarcoma treatment protocol and right lobectomy plus isthmectomy.…”
Section: Discussionmentioning
confidence: 62%
“…12 This unique epithelial tumor, which showed neither C-cell nor follicular cell differentiation, coexisted with papillary thyroid carcinoma (PTC) foci and diffusely expressed cytokeratins and p63, in the absence of vimentin. 12 Since the identification of the expression of cytokeratins in up to 46% of PEEFTs, 13,14 the occurrence of epithelial differentiation in a small cell malignant tumor is no longer a synonym of small cell carcinoma. 14,15 In thyroid, only 3 cases of primary PEEFT 5-7 and 1 case of secondary PEEFT mimicking a thyroid nodule 16 have been described to date.…”
Section: Introductionmentioning
confidence: 99%
“…25 CK19 and EMA expression is uncommon (14.8% and 6.6% respectively). 27,39 Variable expression of tight junction markers such as claudin-1 (63%), zonula-occludens-1 (51%) and occludin (11%) has been reported in ESFT. 42 E-cadherin is negative with the 36B5 clone which targets the extracellular domain.…”
Section: Immunophenotypementioning
confidence: 98%
“…Machado et al (2011) assessed, by genetic analysis, the role of epithelial markers in Ewing’s tumor; the author to show the presence of epithelial markers used antibiotics and an immunohistochemical study in tumor cells. The authors say a statistically significant relationship between the expression of the markers and epithelial cell variants of the tumor is not present, even if they claim that an increased expression is present in these tumors and therefore can be regarded in the diagnosis of the disease (Machado et al, 2011).…”
Section: Ewing Sarcomamentioning
confidence: 99%
“…The authors say a statistically significant relationship between the expression of the markers and epithelial cell variants of the tumor is not present, even if they claim that an increased expression is present in these tumors and therefore can be regarded in the diagnosis of the disease (Machado et al, 2011). …”
Section: Ewing Sarcomamentioning
confidence: 99%